The Organization and Administration of the Cloister in Ancient Babylonia - Harris, Rivkah
A. The Layout of the Cloister Compound B. The Cloister Personnel C. The Administrative Texts of the Cloister D. The Relationship between the Cloister and the Naditus E. The Relationship between the Cloister and the Šamaš Temple F. The Relationship between the Cloister and the Palace.